Discovery and development of brain-penetrant 18F-labeled radioligands for neuroimaging of the sigma-2 receptors - Ying Zhang; Tao Wang; Xiaojun Zhang; Winnie Deuther-Conrad; Hualong Fu; Mengchao Cui; Jinming Zhang; Peter Brust; Yiyun Huang; Hongmei Jia (Elsevier, 2022)
We have discovered and synthesized a series of indole-based derivatives as novel sigma-2 (σ2) receptor ligands. Two ligands with high σ2 receptor affinity and subtype selectivity were then radiolabeled with F-18 in good radiochemical yields and purities, and evaluated in rodents. In biodistribution studies in male ICR mice, radioligand [18F]9, or 1-(4-(5,6-dimethoxyisoindolin-2-yl)butyl)-4-(2-[18F]fluoroethoxy)-1H-indole, was found to display high brain uptake and high brain-to-blood ratio. Pretreatment of animals with the selective σ2 receptor ligand CM398 led to significant reductions in both brain uptake (29%-54%) and brain-to-blood ratio (60%-88%) of the radioligand in a dose-dependent manner, indicating high and saturable specific binding of [18F]9 to σ2 receptors in the brain. Further, ex vivo autoradiography in male ICR mice demonstrated regionally heterogeneous specific binding of [18F]9 in the brain that is consistent with the distribution pattern of σ2 receptors. Dynamic positron emission tomography imaging confirmed regionally distinct distribution and high levels of specific binding for [18F]9 in the rat brain, along with appropriate tissue kinetics. Taken together, results from our current study indicated the novel radioligand [18F]9 as the first highly specific and promising imaging agent for σ2 receptors in the brain.